Methodological strategies used by the teacher to make the irregular verbs recognize student in the affimative e question forms. - Asanza Tarambis, Ingrid Vanessa (Machala : Universidad Técnica de Machala, 2015)
Se requiere el aumento de las estrategias metodológicas actuales, que son importantes para el desarrollo de la silla. Estas estrategias hacen que aprender el idioma, Sin embargo los profesores no se aplican correctamente causando falta de interés en los estudiantes aprendan. La falta de aplicación de los maestros apropiados de estrategias metodológicas, hace que los estudiantes fomentan una actitud causando desmotivación lenguaje inactiva, por lo tanto se pueden considerar otro factor importante que dificulta el proceso de aprendizaje de los estudiantes, la subutilización activa cuando metodologías enseñar.
It requires increasing current methodological strategies, they are important for the development of the chair. These strategies make learning the language, however teachers do not apply correctly causing disinterest in students to learn. The lack of implementation of appropriate teachers by methodological strategies, causes students encourage an inactive attitude causing demotivation language therefore can be considered another important factor hindering the process of student learning, the underutilization active when teach methodologies.
Keywords: METHODOLOGICAL STRATEGY; IRREGULAR VERBS; AFFIRMATIVE FORM; QUESTION FORM